Safety, reactogenicity, and immunogenicity of Ad26.COV2.S co-administered with a quadrivalent standard-dose or high-dose seasonal influenza vaccine: a non-inferiority randomised controlled trialResearch in context - Gabriela Tapia-Calle; Gloria Aguilar; Nathalie Vaissiere; Carla Truyers; Pedro Ylisastigui; Erik Buntinx; Mathieu Le Gars; Frank Struyf; Gert Scheper; Macaya Douoguih; Javier Ruiz-Guiñazú; Robert Patrizi; et al. (EClinicalMedicine)
Summary: Background: Vaccine co-administration can increase vaccination coverage. We assessed the safety, reactogenicity, and immunogenicity of concomitant administration of Ad26.COV2.S COVID-19 vaccine with seasonal influenza vaccines. Methods: This non-inferiority, Phase 3, randomised, double-blind study enrolled 859 healthy adults and was conducted between 02 November 2021 and 28 November 2022. Participants aged ≥18–64 years were randomised to receive a seasonal quadrivalent standard dose (SD) influenza vaccine (Afluria Quadrivalent, Seqirus) concomitantly with Ad26.COV2.S (Coad_SD) or placebo (0.9% NaCl; Control_SD) on Day 1 and placebo or Ad26.COV2.S on Day 29. Participants aged ≥65-years were randomised to the Coad_SD or Control_SD groups, or to Coad_HD or Control_HD groups that received a seasonal quadrivalent HD (high-dose) influenza vaccine (Fluzone High-Dose Quadrivalent, Sanofi Pasteur Inc) in the same schedules. The primary outcomes were haemagglutinin inhibition titres against the four influenza vaccine strains at Day 29, and SARS-CoV-2 Spike-specific antibodies at Day 29 in the Coad_SD group and Day 57 in the Control-SD group, with a non-inferiority margin (Control-SD group/Coad_SD group) of 1.5. Reactogenicity and safety were assessed in all participants (NCT05091307). Findings: Non-inferiority criteria for concomitant administration in the SD groups were met for SARS-CoV-2 Spike-specific antibodies (ratio 1.11, 95% CI 0.97–1.26) and haemagglutinin inhibition titres for all influenza strains (A/H3N2 1.23, 95% CI 1.05–1.45; B/Victoria 0.99, 95% CI 0.84–1.19; B/Yamagata, 1.03, 95% CI 0.88–1.21) except A/H1N1 (1.28, 95% CI 1.09–1.53) for which the upper limit of the 95% CI was >1.5. Concomitant administration of Ad26.COV2.S and SD influenza vaccine induced robust immune responses in terms of SARS-CoV-2 Spike-specific antibodies and haemagglutinin inhibition to all four influenza strains. Seroconversion and seroprotection rates against all influenza vaccine strains were comparable in the Coad and Control groups. Anti-Spike antibodies 28 days after receiving Ad26.COV2.S were similar whether administered with influenza vaccine or alone. Antibody responses persisted at least 6 months post-vaccination in all groups. The reactogenicity and safety profile following co-administration was consistent with the known safety profiles of the study vaccines. No safety concerns were identified. Coadministration was immunogenic and well tolerated in adults aged ≥65 years who received HD influenza vaccine. Interpretation: Co-administration of seasonal influenza vaccine with Ad26.COV2.S was immunogenic with an acceptable safety profile, supporting co-administration of these vaccines. Funding: Janssen Vaccines & Prevention BV and Biomedical Advanced Research and Development Authority.